Health literacy in Korean immigrants at risk for type2 diabetes - Choi, Sarah E. (2013)
Rising incidence of type 2 diabetes (DM) in Korean immigrants has highlighted the need for better prevention efforts. Health literacy is an important predictor in the utilization of preventative health measures, however little is known about health literacy in Korean immigrants. This study examined DM risk factors in a sample of 145 at-risk Korean immigrants, their level of health literacy, and associations between health literacy and DM risk factors. Findings indicated a high prevalence of DM risk factors and a low level of health literacy in the sample. Health literacy was correlated with English proficiency, acculturation, and lower waist to hip ratios among all participants, and with lower blood glucose levels among highly acculturated participants. Korean immigrants who are less acculturated may have lower health literacy than those who are more acculturated. Thus, linguistically and culturally sensitive health education should be incorporated into diabetes prevention efforts.